The relationship between perception of social interaction, perceived social support and social acceptance with aggression among adolescents - Hamid Reza Samadifard; Esmaeil Sadri Damirchi (Gonabad University of Medical Sciences, 2018)
This study was aimed to investigate the relationship between social interaction, perceived social support and social acceptance with aggression among adolescents. The execution method was a descriptive and correlative. The statistical population of this study included all of the boy adolescent high school students, that sample including 260 participants of boy adolescents were chosen from various locations of the city by adopting a cluster sampling technique. Results indicated that among the perception of social interaction elements; there is positive and significant relationship between negative thoughts and aggression, and negative and significant relationship between positive thoughts and aggression. Also, there is negative and significant relationship between the elements of perceived social support (social support of friends, family and others) and regression. Moreover, there is negative and significant relationship between social acceptance and adolescents' aggression. Thus, it can be concluded that perception of social interaction, perceived social support and social acceptance are significant factors which effect the occurrence or absence of adolescents' aggression.